Program Belajar Mengaji Al – Quran dalam Meningkatkan Pemahaman Makhrojul Huruf dan Tajwid Pada Anak di Dusun 1 Desa Riak Siabun I Kecamatan Sukaraja Kabupaten Seluma - H Makmur; Arsyah Salsabilla; Putri Surya Anita; Doci Nurmartha; Gita Arra Hervina; Rina Anjar Wati; Fadila Lesi Sasri; Muhammad Fikri; Muhammad Syahril Sodiqin; Nanda Afriandi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
This research aims to evaluate the effectiveness of the Al-Qur'an learning program implemented in Dusun 1, Riak Siabun I Village. The focus of this research is to assess how the program can improve children's understanding of makhrojul letters and tajwid, as well as identifying factors factors that influence the success or obstacles in its implementation. This method of service is a persuasive method for study participants. The use of this method is considered suitable for subtly inviting or encouraging the general public to take part in an activity. The results of this research show that there are several children who have not mastered the pronunciation of the letters of the Koran and recitation of the Koran well. Apart from that, in this village there is still a lack of facilities and infrastructure as well as teaching staff for Al-Qur'an learning. Based on these findings, we then held a learning program to recite the Koran to improve the understanding of makhrojul letters and tajwid among children in hamlet 1, Riak Sibun 1 village, Sukaraja sub-district, Seluma district.